103 A PROSPECTIVE STUDY TO EVALUATE THE INCIDENCE OF HIGH LEVELS OF METHEMOGLOBIN IN PATIENTS USING A NEW PULSE CO-OXIMETER. Issue 1 (1st January 2007) - Kim, P.; Macknet, M. R.; Kimball-Jones, P.; Martin, R. D.; Allard, M.
Abstract : Methemoglobin is hemoglobin with iron in a ferric state instead of a ferrous state, thus unable to carry oxygen causing cyanosis and a left shift of the oxyhemoglobin dissociation curve. Methemoglobinemia, either congenital or acquired, is a rare clinical occurrence and can be life threatening for individuals with levels greater than 20%. Acquired methemoglobinemia has multiple etiologies and is commonly caused by topical anesthetic drugs such as benzocaine, prilocaine, and lidocaine. Nitrates, both topical and intravenous, can also precipitate clinically significant levels. The inherited form of methemoglobinemia is rare and generally presents early in life. Until recently, the only method for measuring methemoglobin levels was to send a blood sample for co-oximetry analysis. Conventional dual-wavelength pulse oximetry does not detect methemoglobin levels and its mearsurement of oxygen saturation becomes unreliable in the setting of even small levels of methemoglobin in the blood. Recently, a new mutiwavelength pulse co-oximeter was developed that enables the detection of methemoglobin and carboxyhemoglobin (Masimo RAD 57 pulse co-oximeter, Irvine, CA). After institutional review board approval, we performed a prospective study to determine the incidence of elevated methemoglobin levels in 500 patients on medications known to cause elevations in methemoglobin levels. All patients were screened using the new pulse co-oximeter to determine the methemoglobin levels. Patients with clinically significant elevations in methemoglobin levels were referred to clinicians for further evaluation and treatment. Of the patients screened, 498 patients had clinically insignificant methemoglobin levels. Two patients exposed to benzocaine, a topical anesthetic, were found to have serious elevations in methemoglobin levels. One patient with benzocaine toxicity was found to have initial methemoglobin levels of 38.9 to 45.8% using the pulse co-oximeter. This level was confirmed with co-oximetry analysis. The second patient was discovered just after the initiation of methylene blue therapy for a methemoglobin level of 24%. The results of this study demonstrate the need to monitor patients exposed to triggering medications. Both patients with elevated methemoglobin levels were successfully treated. Of these patients with benzocaine toxicity only one of them was recognized by clinicians prior to diagnosis using the pulse co-oximeter. The pulse co-oximeter is portable and small; it provides an opprtunity for early noninvasive diagnosis of high methemoglobin level at a low cost.